Penyuluhan Perilaku Hidup Bersih dan Sehat Sebagai Upaya Promotif dalam Meningkatkan Pengetahuan Masyarakat di Kelurahan Buaran Indah - Adawiyah, Siti Robeatul; Rahmawati, Rista Nova; Ainurjanah, Candrawati; Herliyanti, Dita Rizki; Santi, Dwi Ros; Nuradini; Aini, Nurul; Hendrayani, Pajar; Lestari, Puji Ardi; Suryaniaga; Hidayat, Sutiawati; Rahmanil Aisy, Syifaa’ur (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Clean and Healthy Living Behavior (PHBS) is an approach that promotes good habits to maintain cleanliness and health in daily life. essential promotive and preventive effort to improve public health. However, its implementation remains inconsistent due to varying levels of knowledge, awareness, and environmental factors among communities. Objective: The goal of this service was to boost people's understanding and awareness. regarding PHBS through an interactive health education activity in Buaran Indah Urban Village, Tangerang City. Method: This public service was conducted using a participatory method involving health education through leaflets, demonstrations, and discussion sessions. A pre-test and post-test were conducted to check how much the 50 participants knowledge improved. Result: The results showed a significant increase in participants’ knowledge after the counseling session. Pre-test scores ranged 48,8% answering correctly per question, while post-test scores increased to 90,0%. Initial survey data also showed that while 100% of households used proper latrines and disposed of wastewater properly, 6% still burned household waste, and 41.6% drank less than 8 glasses of water daily. Conclusion: PHBS counseling was effective in increasing participants’ understanding and awareness. Direct, participatory health education interventions can serve as a strategic approach in promoting public health behavior at the community level.